2012
DOI: 10.3928/01477447-20121023-26
|View full text |Cite
|
Sign up to set email alerts
|

Level of Billing as a Function of Resident Documentation and Orthopedic Subspecialty at an Academic Multispecialty Orthopedic Surgery Practice

Abstract: Documentation, coding, and billing for physician-patient encounters have evolved over time and have significant variability. Appropriate and complete documentation of these encounters can contribute to the financial viability of private and academic medical centers. The objectives of this study were to assess the financial effect of documentation on billing and to compare the authors' institution's distribution of billing level compared with Medicare normative data. Four orthopedic surgery subspecialty clinics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…Furthermore, this finding proved to exist across years of training and in 9 out of 10 classes. Our study is consistent with previous literature in this area [ 2 , 12 ]. Evans et al showed similar patterns using aggregate billing data.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, this finding proved to exist across years of training and in 9 out of 10 classes. Our study is consistent with previous literature in this area [ 2 , 12 ]. Evans et al showed similar patterns using aggregate billing data.…”
Section: Discussionsupporting
confidence: 94%
“…This pattern of residents using lower E/M codes is not limited to family medicine; Dezfuli and Smith compared resident billing to Medicare normative data and also documented higher percentages of level 3 E/M codes among resident billings. 2 Both studies claimed significant losses of revenue [ 2 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies across a range of specialties suggest similar needs for increased practice administration training during residency. This shortcoming in current residency training and graduate experience has been reported in Orthopedics, 14 Neurology, 15 Dermatology, 16 and Otolaryngology. 17 Including practice management within the curriculum of a residency program allows trainees a mentored environment for learning key principles, and an opportunity to apply them in a semi-autonomous setting; thus a residency graduate---regardless of eventual practice type or setting---will possess key knowledge in these important areas.…”
Section: Discussionmentioning
confidence: 92%
“…Fewer studies have examined the impact of inpatient EHRs, and some healthcare systems have been hesitant to adopt them because they are expensive and potentially cumbersome [9,10]. Examination of the effect of inpatient EHRs on documentation coding levels and professional fee reimbursement are sparse [11,12] We investigated the impact of an inpatient EHR on coding levels and reimbursement for a busy trauma and emergency surgery service at a large teaching hospital. Trauma and emergency surgery is the ideal type of surgical service to study because of the high percentage of inpatient cognitive evaluation and management work done by the average trauma and emergency surgeon relative to other surgical specialties [13].…”
Section: Introductionmentioning
confidence: 99%